Fuzzy-based conflict resolution management of groundwater in-situ bioremediation under hydrogeological uncertainty - Taravatrooy, Narges; Nikoo, Mohammad Reza; Adamowski, Jan Franklin; Khoramshokooh, Nafiseh (Journal of Hydrology, 2019)

Regionalization of flood magnitudes using the ecological attributes of watersheds - Jabbarian Amiri, Bahman; Baheri, Bahareh; Fohrer, Nicola; Adamowski, Jan Franklin (Geocarto International, 2020)

An Entropy-Based Approach to Fuzzy Multi-objective Optimization of Reservoir Water Quality Monitoring Networks Considering Uncertainties - Pourshahabi, Shokoufeh; Nikoo, Mohammad Reza; Raei, Ehsan; Adamowski, Jan Franklin (Water Resources Management, 2018)

Probabilistic Event Based Rainfall-Runoff Modeling Using Copula Functions - Abdollahi, Sajjad; Akhoond-Ali, Ali Mohammad; Mirabbasi, Rasoul; Adamowski, Jan Franklin (Water Resources Management, 2019)

A critical review on the application of the National Sanitation Foundation Water Quality Index - Noori, Roohollah; Berndtsson, Ronny; Hosseinzadeh, Majid; Adamowski, Jan Franklin; Abyaneh, Maryam Rabiee (Environmental Pollution, 2019)

Correction to: Analysis of deterministic and geostatistical interpolation techniques for mapping meteorological variables at large watershed scales - Amini, Mohammad Amin; Torkan, Ghazale; Eslamian, Saeid; Zareian, Mohammad Javad; Adamowski, Jan Franklin (Acta Geophysica, 2019)

Analysis of deterministic and geostatistical interpolation techniques for mapping meteorological variables at large watershed scales - Amini, Mohammad Amin; Torkan, Ghazale; Eslamian, Saeid; Zareian, Mohammad Javad; Adamowski, Jan Franklin (Acta Geophysica, 2019)

Relationship between water quality and macro-scale parameters (land use, erosion, geology, and population density) in the Siminehrood River Basin - Bostanmaneshrad, Farshid; Partani, Sadegh; Noori, Roohollah; Nachtnebel, Hans-Peter; Berndtsson, Ronny; Adamowski, Jan Franklin (Science of The Total Environment, 2018)

Soil Erosion in the United States. Present and Future (2020-2050) - Shojaeezadeh, Shahab Aldin; Al-Wardy, Malik; Nikoo, Mohammad Reza; Mooselu, Mehrdad Ghorbani; Alizadeh, Mohammad Reza; Adamowski, Jan Franklin; Moradkhani, Hamid; Alamdari, Nasrin; Gandomi, Amir H. (2022)
Soil erosion is a significant threat to the environment and long-term land management around the world. Accelerated soil erosion by human activities inflicts extreme changes in terrestrial and aquatic ecosystems, which is not fully surveyed/predicted for the present and probable future at field-scales (30-m). Here, we estimate/predict soil erosion rates by water erosion, (sheet and rill erosion), using three alternative (2.6, 4.5, and 8.5) Shared Socioeconomic Pathway and Representative Concentration Pathway (SSP-RCP) scenarios across the contiguous United States. Field Scale Soil Erosion Model (FSSLM) estimations rely on a high resolution (30-m) G2 erosion model integrated by satellite- and imagery-based estimations of land use and land cover (LULC), gauge observations of long-term precipitation, and scenarios of the Coupled Model Intercomparison Project Phase 6 (CMIP6). The baseline model (2020) estimates soil erosion rates of 2.32 Mg ha 1 yr 1 with current agricultural conservation practices (CPs). Future scenarios with current CPs indicate an increase between 8% to 21% under different combinations of SSP-RCP scenarios of climate and LULC changes. The soil erosion forecast for 2050 suggests that all the climate and LULC scenarios indicate either an increase in extreme events or a change in the spatial location of extremes largely from the southern to the eastern and northeastern regions of the United States.
Keywords: Infolettre; Infolettre_Ete_2024